Weblogs for English language learning: students' perceptions - Wan, Juida; Tan, Bee Hoon (Anadolu University, 2011)
The digital explosion of information on the Internet has resulted in a need for a new and up-to-date way for Digital Natives to learn English. Educators have reported numerous benefits of using weblogs in English language learning. This article presents a small scale study on the use of weblogs for English language learning at tertiary level in Malaysia. Twenty six students kept weblogs for a duration of a semester. This study investigated how students perceived the use of weblogs for English language learning. A questionnaire which was made up of both close-ended and open-ended questions was administered at the end of the study. A mixture of quantitative and qualitative methods was used to analyse the students' responses to the questionnaire. The study found that students were aware of their audience when they blogged and that they geared their writing towards their audience. In addition, they also interacted with others through the use of the comment feature on their weblogs. Furthermore, the majority of the students enjoyed blogging and found weblogs useful for English language learning. This study found that weblogs are promising interactive tools for English language learning.